2022
DOI: 10.1071/cp21619
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma application improves germination, establishment and productivity of Gatton panic grass (

Abstract: Megathyrsus maximus (Gatton panic) is a tropical grass highly valued both for its use as forage and for its biofuel potential. A major constraint in establishing pastures of this cultivar is the low viability and germination of seeds and the poor initial seedling establishment. We used non-thermal plasma (NTP, partially ionised gas) as a novel technology to treat seeds of this grass, aiming to improve their quality (i.e. germination traits). We also followed the performance of seedlings grown from NTP-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Conversely, Pérez Pizá et al have found improved seedling establishment parameters, such as dynamics of cumulative emergence, emergence coefficient, and weighted average emergence rate, after nitrogen DBD plasma treatment of Gatton panic ( Megathyrsus maximus ) grass seeds. This indicates that, compared to control seeds, seedlings emerged from plasma-treated seeds both earlier and in greater numbers [ 12 ]. Interestingly, in a publication concerning buckwheat, plasma treatment of seeds decreased the number of emerged seedlings but at the same time greatly improved plant growth and yield [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Pérez Pizá et al have found improved seedling establishment parameters, such as dynamics of cumulative emergence, emergence coefficient, and weighted average emergence rate, after nitrogen DBD plasma treatment of Gatton panic ( Megathyrsus maximus ) grass seeds. This indicates that, compared to control seeds, seedlings emerged from plasma-treated seeds both earlier and in greater numbers [ 12 ]. Interestingly, in a publication concerning buckwheat, plasma treatment of seeds decreased the number of emerged seedlings but at the same time greatly improved plant growth and yield [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high electron temperature during the discharge process, the temperature of the heavy particles remains low, creating a system characterized by a low-temperature state, called low-temperature (non-thermal) plasma [10]. Nonthermal plasma (NTP) is a novel and promising agricultural technology that can improve plant performance by modulating gene expressions associated with seed germination, plant immune responses to abiotic stresses, pathogen resistance, and growth regulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…With so much knowledge about NTP and its established diverse applications, the focus has also shifted towards the agriculture sector (known as ‘plasma agriculture’ [ 31 ]) in recent years, as there are calls for new and clean technologies to replace chemical pesticides that are growing around the world. Several research articles have demonstrated that NTP can potentially improve seed germination and crop yield [ 32 , 33 , 34 , 35 , 36 ]. Although it is evident that NTP undoubtedly works well in the enhancement of different crop traits, we shift our focus onto the main topic of this review which is the effective use of NTP in plant protection, especially against Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%